Identification of key rearing factors to manage cattle carcass fatness and conformation scores during the fattening period. Issue 1 (2nd January 2019) - Soulat, Julien; Monteils, Valérie; Léger, Stéphanie; Picard, Brigitte
Abstract: The fatness and conformation scores characterise the payment of cattle carcasses in the EUROP system. The management of these carcass traits is important for stakeholders of the meat chain. The aim of this study was to identify rearing factors, applied during the fattening period, influencing the fatness and conformation scores of the carcasses, in two categories of animals (cull cows and young bulls). A data set of individual cattle data (233 cull cows and 565 young bulls) from different experiments was used. It included eleven rearing factors characterising the fattening period. From carcass data, clusters of fatness and conformation scores were defined. To identify the rearing factors with a leverage on carcass traits according to the category of animal, four robust prediction models were developed using logistic regression to predict these clusters. According to the results of the models established, to achieve the fatness score rehearsed by stakeholders, cull cows should ingest less dry matter (DM) and have a shorter fattening period, whereas young bulls should be more efficient, ingest more DM and be slaughtered heavier. To improve the carcass conformation score, the cull cows should ingest more net energy and begin their fattening heavier. For the young bulls, the three rearing factors identified for the fatness score allowed to improve the conformation score. This study showed also that the jointly management of these both carcass traits is possible, nevertheless it is necessary to adapt the applied fattening practices according to the category of animal. Highlights: Used rearing factors to predict the fat score and conformation of bovine carcasses. Logistic regression is well adapted to predict fat score and conformation of bovine carcasses. The prediction models of the fat score and conformation are robust.